2021
DOI: 10.5216/ree.v23.66979
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do suporte social e da adesão medicamentosa em pacientes com doença arterial coronariana

Abstract: Objetivo: Avaliar a adesão medicamentosa e o suporte social percebido e sua associação em pacientes hospitalizados por Doença Arterial Coronária. Método: Estudo transversal envolvendo pacientes hospitalizados por Síndrome Coronariana Aguda ou Crônica. A adesão medicamentosa foi avaliada pelo Brief Medication Questionnaire e o suporte social pela Escala de Apoio Social do Medical Outcomes Study. Valor p<0,05 foi considerado como significativo. Resultados: Incluídos 59 pacientes, sendo que 50,8% for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Of these, 72.72% stopped taking the drug for less than three days (MEDEIROS and VIANNA, 2006). In a meta-analysis of 376,162 patients, Sayed relate that after 24 months, non-adherence to treatment was 43% (SAYED et al, 2012), while Hermano found 50.8% classified as potentially nonadherent and 37.7% as non-adherent to treatment (HERMANO et al, 2021). Coleta affirms that non-adherence could be related to behavioral factors (COLETA et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Of these, 72.72% stopped taking the drug for less than three days (MEDEIROS and VIANNA, 2006). In a meta-analysis of 376,162 patients, Sayed relate that after 24 months, non-adherence to treatment was 43% (SAYED et al, 2012), while Hermano found 50.8% classified as potentially nonadherent and 37.7% as non-adherent to treatment (HERMANO et al, 2021). Coleta affirms that non-adherence could be related to behavioral factors (COLETA et al, 2010).…”
Section: Discussionmentioning
confidence: 96%